Gallbladder carcinoma presenting as hemorrhagic cholecystitis in a patient living with HIV: a diagnostic challenge - Gowshika Seetharaman; Anand Lakshmanan; Selvaganesh Chandrasekaran; Chandrabose Ambedkar (International Surgery Journal, 2026)
Hemorrhagic cholecystitis is an uncommon but potentially life-threatening surgical emergency characterized by hemorrhage into the gallbladder lumen. Although it is usually associated with severe inflammation, trauma, anticoagulant therapy, or vascular disorders, its occurrence secondary to gallbladder carcinoma is exceedingly rare. Intraluminal hemorrhage may obscure an underlying malignancy, posing a diagnostic challenge. A 39-year-old woman living with HIV on antiretroviral therapy presented with severe right upper quadrant pain and fever of one day's duration. Ultrasonography and contrast-enhanced computed tomography demonstrated a markedly distended gallbladder with heterogeneous hyperdense intraluminal contents, suggestive of hemorrhagic acalculous cholecystitis. In view of the acute abdomen, an emergency open cholecystectomy was performed. The gallbladder was grossly distended and contained approximately 100 ml of organized blood clot. Gross examination of the resected specimen revealed an irregular intraluminal mass. Histopathological examination demonstrated a poorly differentiated gallbladder carcinoma invading the muscular layer (pT1b). Retrospective review of the preoperative CT images revealed an enhancing intraluminal lesion that had been masked by hemorrhagic contents. Gallbladder carcinoma should be considered in patients presenting with hemorrhagic cholecystitis, particularly when imaging demonstrates focal intraluminal abnormalities. This case highlights the diagnostic challenge posed by intraluminal hemorrhage and underscores the importance of meticulous gross examination and routine histopathological evaluation of all cholecystectomy specimens to identify occult malignancy.